2003
DOI: 10.1074/jbc.m300671200
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 Stimulates Bone Sialoprotein (BSP) Expression through cAMP and Fibroblast Growth Factor 2 Response Elements in the Proximal Promoter of the Rat BSP Gene

Abstract: Bone sialoprotein (BSP), an early marker of osteoblast differentiation, has been implicated in the nucleation of hydroxyapatite during de novo bone formation. Prostaglandin E 2 (PGE 2 ) has anabolic effects on proliferation and differentiation of osteoblasts via diverse signal transduction systems. Because PGE 2 increases the proportion of functional osteoblasts in fetal rat calvarial cell cultures, we investigated the regulation of BSP, as an osteoblastic marker, by PGE 2 . Treatment of rat osteosarcoma UMR 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 63 publications
(55 reference statements)
2
69
1
1
Order By: Relevance
“…In nuclei, FHL2 is known to function as a co-activator for several transcription factors including CREB, AP-1, androgen receptor, and ␤-catenin. (16)(17)(18)(19)(20)(21)(22) Because these transcription factors and integrins play critical roles in osteoblast function and bone formation, (2,6,(46)(47)(48)(49)(50)(51) the enhancement in activities of these transcription factors and integrins by FHL2 may explain, at least in part, the osteogenic effect of FHL2. The stimulation of osteoblast specific transcription factor Osx lends additional support to the osteogenic effect of FHL2.…”
Section: Discussionmentioning
confidence: 99%
“…In nuclei, FHL2 is known to function as a co-activator for several transcription factors including CREB, AP-1, androgen receptor, and ␤-catenin. (16)(17)(18)(19)(20)(21)(22) Because these transcription factors and integrins play critical roles in osteoblast function and bone formation, (2,6,(46)(47)(48)(49)(50)(51) the enhancement in activities of these transcription factors and integrins by FHL2 may explain, at least in part, the osteogenic effect of FHL2. The stimulation of osteoblast specific transcription factor Osx lends additional support to the osteogenic effect of FHL2.…”
Section: Discussionmentioning
confidence: 99%
“…HA, U0126 and LY294002 have been shown to inhibit the increased binding activities of transcription factors to the FRE and HOX elements in the rat BSP gene promoter (35). In our previous study, we showed that FGF2 stimulated BSP gene transcription via the tyrosine kinase and ERK1/2 pathways (33), PTH activated cAMP and phospholipase C through the PKA and tyrosine kinase pathways (31), and PGE2 increased BSP transcription via PKA, tyrosine kinase and ERK1/2, which target nuclear proteins binding to CRE and FRE in the rat BSP gene promoter (34). PI3K/Akt is one of the critical pathways for differentiation of skeletal component cells, such as chondrocytes, osteoblasts, myoblasts and adipocytes (52).…”
Section: Discussionmentioning
confidence: 99%
“…In the human BSP gene promoter, an inverted TATA box (nts -28~-23) (27) and an inverted CCAAT box (nts-54~-50) maintain basal transcription (29,30), and two cAMP response elements (CRE1; -79~-72, CRE2; -674~-667) are also present (31,32). Additionally, a fibroblast growth factor 2 (FGF2) response element (FRE; nts -96~-89) (33,34), three activating protein 1 (AP1) response elements (AP1(1); -148~-142, AP1(2); -483~-477 and AP1(3); -797~-791) (31,32), and a homeobox binding site (HOX; -200~-191) (35,36) have been characterized.…”
Section: Introductionmentioning
confidence: 99%
“…FGF2 increased BSP transcription via FGF2 response element (FRE) in the proximal promoter of the rat BSP gene, which regulates both basal and FGF2-induced BSP transcription (10). We have also reported that the activator protein 1 (AP1) element is another target of FGF2 in the context of BSP transcription (11), and that in addition prostaglandin E 2 induces BSP gene expression through a cAMP response element (CRE) and FRE in the proximal promoter of the rat BSP gene (12).…”
Section: Introductionmentioning
confidence: 99%
“…These promoters include an inverted TATA box (-24 to -19) (27) and an inverted CCAAT box (-50 to -46) (28,29). Furthermore, a CRE (-75 to -68) (12,30), a FRE (-92 to -85) (10,12,31,32), a pituitary specific transcription factor-1 (Pit-1) motif (-111 to -105) (33,34), a homeodomain protein binding site (HOX; -199 to -192) (35,36), a transforming growth factor beta (TGF-β) activation element (-499 to -485) (35,37) and a glucocorticoid response element (GRE; -920 to -906) overlapping with AP1 (-921 to -915) have been characterized (14,38).…”
Section: Introductionmentioning
confidence: 99%